2017
DOI: 10.1371/journal.pone.0181542
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mangiferin on skin: Penetration, permeation and inhibition of ECM enzymes

Abstract: Mangiferin (2-C-β-D-glucopyranosyl-1,3,6,7-tetrahydroxyxanthone) is a polyphenol with strong antioxidant properties. Mangiferin is obtained from the mango tree (Mangifera indica L., Anacardiaceae). It has been proven that mangiferin exhibits many pharmacological activities. The aim of this study was to analyze the penetration of mangiferin into the human skin and through the skin. According to our knowledge, skin penetration and permeation studies of mangiferin have not been analyzed so far. Additionally, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 35 publications
(35 reference statements)
1
49
0
2
Order By: Relevance
“…[52] Previous studies reported that F I G U R E 4 EDX spectrum of Ag nanoparticles F I G U R E 5 Anticancer assay of AgNWs mediated green synthesis silver nanoparticles HeLa and HT-29 cell lines phenolic compounds such as caffeine, catechin, epigallocatechin gallate, and mangiferin has inhibited ChC enzyme activity depending on various concentrations. [53][54][55][56][57]…”
Section: Effect Of Agnws On Collagenase Activitymentioning
confidence: 99%
“…[52] Previous studies reported that F I G U R E 4 EDX spectrum of Ag nanoparticles F I G U R E 5 Anticancer assay of AgNWs mediated green synthesis silver nanoparticles HeLa and HT-29 cell lines phenolic compounds such as caffeine, catechin, epigallocatechin gallate, and mangiferin has inhibited ChC enzyme activity depending on various concentrations. [53][54][55][56][57]…”
Section: Effect Of Agnws On Collagenase Activitymentioning
confidence: 99%
“…The main barrier for xenobiotic absorption through the skin is the stratum corneum. Research has revealed the ability of mangiferin to reversibly inhibit elastase and collagenase activity, as well as to permeate the stratum corneum and pass into the epidermis and dermis (115). As the fat and water distribution coefficient of mangiferin is relatively high, oral absorption is low (9), which suggests that mangiferin may be better absorbed through the skin.…”
Section: Other Properties Of Mangiferinmentioning
confidence: 99%
“…e precision and accuracy were analyzed by the QC samples at three concentrations (3,160, and 480 ng/mL). e intraday and interday precision and accuracy were determined by analyzing six replicates of plasma samples on the same day and three consecutive days, respectively.…”
Section: Precision and Accuracymentioning
confidence: 99%
“…Mangiferin (MG, Figure 1), 1,3,6,7-tetrahydroxyxanthone-C2-β-D glucoside, is a type of xanthone derivative found in Mangifera indica L., Anemarrhena asphodeloides Bunge, and other plants [1][2][3][4][5]. Recent studies showed that MG has multiple beneficial biological activities, including antidiabetes, antioxidation, antitumor, anti-inflammation, immunoregulation, antipyretic, antibacterial, memory improvement, and prevention of ultraviolet-induced skin aging [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%